Dependable distributed OSGi environment - Matos, Miguel (2008)
As the concept of Service Oriented Computing matures the need for well defined architectures and protocols to address this trend is essential if IT is going to properly embrace SOC. The SOC paradigm has several requirements to work properly such as service composition and cooperation in a loosely coupled fashion, ability to adapt autonomously to environmental and business changes and address concerns such as modularity, dynamicity and proper integration between services. The popularization of the OSGi platform its another effort towards the SOC paradigm by issuing key aspects such as modularity and dynamicity in its service oriented design. However there is much room for improvement namely on the creation of architectures and mechanisms to improve the dependability of the overall solution by strengthening key properties such as the availability, reliability, integrity, safety and maintainability of the platform. In this work we propose a middleware layer that offers the strong modular and dynamic properties required in an SOC environment by relying on OSGi while addressing dependability concerns. The starting point to achieve this is by instrumenting an OSGi implementation and providing means to monitor and manage it accordingly to business and environmental requirements. By relying on group communication facilities and some properties from the OSGi specification we are able to migrate OSGi environments between nodes thus minimizing service delivery disruption in the presence of faults and addressing, at the same time SLA properties by migrating (or shutting down) services that are consuming more resources than agreed/expected.